Final answer:
To determine p(O|(A∩B)), we can use Bayes' theorem. Bayes' theorem states that p(O|(A∩B)) = (p(A∩B|O) * p(O)) / p(A∩B). To calculate this, we need to find p(A∩B|O) and p(A∩B).
Step-by-step explanation:
To determine p(O|(A∩B)), we can use Bayes' theorem. Bayes' theorem states that p(O|(A∩B)) = (p(A∩B|O) * p(O)) / p(A∩B). To calculate this, we need to find p(A∩B|O) and p(A∩B).
We are given that A and B are conditional independent events given O and ~O, which means p(A|O) = p(A) and p(B|~O) = p(B). Thus, p(A∩B|O) = p(A|O) * p(B|O) = 0.8 * 0.75 = 0.6. Now, to find p(A∩B), we can use the formula p(A∩B) = p(A) * p(B). We are not given p(A), so we cannot calculate p(A∩B).